INTRODUCING STANDARD UNIT OF VOLUME MEASUREMENT WITH ETHNOMATHEMATICS FOR ELEMENTARY SCHOOL STUDENTS - Ernawati, .; Kurniawati, . (PEOPLE: International Journal of Social Sciences, 2017)
Apperception is the main part of the learning process. It brings students to the good condition to be ready to learn something new. Meanwhile, ethnomathematics is one of the learning methods combining math with culture. It is one of learning based on contextual which is culture as the context. It can be included to make a good apperception for students. Therefore, this research aimed to present how to use ethnomathematics in the learning process in order to bridge elementary students in understanding units of measurement. This research includes as descriptive research to find ethnomathematics in the unit of measurement and how to use it in the learning process. The population of this study was areas in Central Java, whereas the research samples were randomly selected areas that represent the population. Data collection was conducted by interview method. Then, the data found were analyzed. The selected analytical technique is a descriptive analysis describing the units used by society in measuring the volume of certain objects. The form of ethnomathematics found in Central Java is a community activity that uses several terms to give a unit of measure of volume to a particular object. These terms can be used in learning mathematics, especially in apperception, with the aim of presenting the mathematical context that is appropriate to everyday life.